Re-reading the poem “Sea” of Josip Pupačić - Lemac, Tin (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The paper offers a new reading of Josip Pupačić’s anthology poem Mora (1955: 31) and thereby complements the previous reading present in the author’s monograph “Poetic symmetries in the poetry of Josip Pupačić” (Lemac 2017). This reading is based on consideration of Pupačić’s poetry in the poetry collection “Mladići” (1955), as well as a review and critical observation of previous readings of the said poem. The poem is interpreted as a magical act of discursivization of the entity of the sea. This act is observed through the analysis of the text itself and intertextual relations with the original poetry. The concluding considerations offer premises on the dialectical relationship of discursing the sea as a poetic image and metaphor. The theoretical-methodological apparatus unites the methods of literary stylistics, literary anthropology and the theory of intertextuality.